2012
DOI: 10.1007/978-1-4614-4989-8_12
|View full text |Cite
|
Sign up to set email alerts
|

NIRS Measurements with Elite Speed Skaters: Comparison Between the Ice Rink and the Laboratory

Abstract: Wearable, wireless near-infrared (NIR) spectrometers were used to compare changes in on-ice short-track skating race simulations over 1500m with a three-minute cycle ergometry test at constant power output (400W). The subjects were six male elite short-track speed skaters. Both protocols elicited a rapid desaturation (∆TSI%) in the muscle during early stages (initial 20s), however asymmetry between right and left legs was seen in ΔTSI% for the skating protocol, but not for cycling. Individual differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
(13 reference statements)
1
17
0
Order By: Relevance
“…However, a small knee angle also seems to lead to a reduced blood flow to the working muscles, resulting in a deoxygenation of these muscles [40]. This reduced blood flow in speed skating is supported by several studies involving (elite) short-track speed skaters [65][66][67][68]. The strong relationship between deoxygenated haemoglobin of the exercising quadriceps and lactate concentration, but not to the whole body VO 2, showed that the high lactate concentrations in (short-track) speed skating were caused by a reduced blood flow to the working muscles and not by the VO 2 of the athlete's whole body [65].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, a small knee angle also seems to lead to a reduced blood flow to the working muscles, resulting in a deoxygenation of these muscles [40]. This reduced blood flow in speed skating is supported by several studies involving (elite) short-track speed skaters [65][66][67][68]. The strong relationship between deoxygenated haemoglobin of the exercising quadriceps and lactate concentration, but not to the whole body VO 2, showed that the high lactate concentrations in (short-track) speed skating were caused by a reduced blood flow to the working muscles and not by the VO 2 of the athlete's whole body [65].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, they showed that the asymmetry was due to the specific demands of short-track speed skating and was not an intrinsic difference between the right and left quadriceps of the selected group [68]. Interestingly, although an asymmetry in muscle oxygenation during long-track speed skating was also reported, the difference in oxygenation between the legs was only the result of a difference in the initial desaturation between both legs directly after the start [43], while the short-track studies reported a similar initial desaturation in both legs followed by an asymmetry in deoxygenation during the race [66,67].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Near-infrared spectroscopy (NIRS) is nowadays a wellaccepted technology to assess muscle oxygenation in vivo, and our previous research 18,19 together with studies conducted by others (for a review of this methodology see Ferrari et al 20 ) suggest that this technology could be implemented successfully in most sports, including aquatic sports. 21 While the market seems to be showing an increase in portable NIRS devices, only few present some form of validation to date.…”
Section: Cardiovascular and Respiratory Measurementsmentioning
confidence: 98%